Cover Feature: Low‐Cost and Scalable Ni‐Prussian Blue Analogue//Functionalized Carbon Based Na‐Ion Systems for all Climate Operations (ChemPhysChem 4/2023). Issue 4 (14th February 2023) - Naskar, Pappu; Debnath, Subhrajyoti; Maiti, Apurba; Biswas, Biplab; Banerjee, Anjan
Abstract : The Cover Feature illustrates a high‐power Na‐ion battery, which can operate in both hot and cold climates, with reasonably low cost compared to the state‐of‐the‐art batteries. This device is fabricated with Prussian blue framework positive and carbon black negative electrodes in aqueous electrolyte medium. More information can be found in the Research Article by Anjan Banerjee and co‐workers .